KEARIFAN LOKAL DALAM STRUKTUR SOSIAL MASYARAKAT KAMPUNG NAGA: IMPLIKASI BAGI PENDIDIKAN KEWARGANEGARAAN - Dede Kurniawan; Rini Oktaviani; Muhammad Fajar Firdausyi; Heri Ginanjar; Sobali Suswandy (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Kampung Naga, an indigenous community located in West Java, Indonesia, has a unique social structure rooted in local wisdom values. This study identifies various aspects of local wisdom, such as customs, norms, and social practices that shape the social structure in Kampung Naga. The research examines the role of local wisdom in the social structure of the indigenous community in Kampung Naga and its implications for citizenship education. Through a qualitative case study approach, the study explores how this local wisdom influences the concept of citizenship and community participation within the educational context. Findings indicate that local wisdom plays a crucial role in shaping collective identity and reinforcing social responsibility. The implications for citizenship education include integrating local wisdom values into the curriculum to enhance understanding and active student participation in national life. The study suggests the need for a more context-sensitive approach in developing citizenship education materials to promote values of diversity and tolerance.